SIMILAR PROPERTIES AND GENETIC PARAMETERS OF LOCAL VARIETIES OF GOGO RICE - Samudin, Sakka (International Journal of Research -GRANTHAALAYAH, 2023)
The genetic resources of food plants are an indispensable asset for the formation or improvement of the characteristics of superior varieties. These genetic resources continue to experience erosion due to modern agricultural practices, so they must be preserved through exploration, characterization, and estimation of genetic parameters. This study aims to determine the similarity of traits and genetic parameters of local upland rice varieties. The experiment was conducted at the Sidondo experimental garden, Sidondo Village, Tambubulava District, Sigi Regency, from April to August 2019. The study used a Randomized Block Design with 24 local varieties as the treatment, which was repeated three times so that there were 72 experimental plots. The cluster analysis results showed 3 clusters of grouping varieties, namely one variety for cluster 1, 6 types for cluster 2, and 17 combinations for cluster 3. 10 traits had high coefficients of genetic diversity. The number of seeds per panicle, leaf area, plant height, number of tillers, leaf length, flowering age, and stem diameter are traits with high heritability and genetic progress. The number of productive tillers is a trait with a simple correlation value and a heightened direct effect on yield, so indirect selection can be made to increase upland rice yield.